PENGARUH KONSENTRASI AIR LERI TERHADAP PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS JAMUR TIRAM (Pleurotus ostreatus Jacq. Ex Fr) - Suprapto, Suprapto; Rosmiah, Rosmiah; Gusmiatun, Gusmiatun (Universitas Muhammadiyah Palembang, 2017)
The impact of leri water concentrate on the growth and production of some varieties of oyster mushroom (Pleurotes ostreatus Jacq. Ex Fr). The purposes of this research Is to determine the concentrate of leri water that can produce the growing of oyster mushroom and also the best production of some kind of oyster mushroom. this research was conducted in farmers’ field of jamur tiram Jl. Rawa Sari Rt. 40 Rw 10 Kel. Bukit Sangkal Celentang, District Kalidoni Palembang. This research used a randomize block design/Random group design (RAK) factorial with 12 combination treatment that was repeat as much as 3 times. The first factor is water L4=60 ml/l liter of water . the second factor is varieties of oyster mushroom (V) : V1 = white oyster mushroom, V2 = pink oyster mushroom, V3 = oyster mushroom brown. The changing that was observed is harvest time (days) and how many oyster mushroom that will growing in one clump (fruit), maximum width of the hood (cm) and the total weight of the oyster mushroom growing (g). The results showed that the provision of water treatment tabulation leri 60 ml / l of water provide the best growth and production of weighing 285.77 g total weight. Treatment of white oyster mushroom varieties give the best effect on the number of fruiting bodies of fungi, mildew fruit hood width and total weight of fruit fungus. In the tabulation of the interaction between the provision of water treatment leri 60 ml / l of water with white oyster mushroom varieties good influence on the growth and production.